Template-Free Electrochemical Deposition of t-Se Nano- and Sub-micro Structures With Controlled Morphology and Dimensions - Seyedmahmoudbaraghani, Saba; Yu, Sooyoun; Lim, Jaehong; Myung, Nosang V. (Frontiers in Chemistry, 2020)
Selenium, depending on its crystal structure, can exhibit various properties and, as a result, be used in a wide range of applications. However, its exploitation has been limited due to the lack of understanding of its complex growth mechanism. In this work, template-free electrodeposition has been utilized for the first time to synthesize hexagonal-selenium (t-Se) microstructures of various morphologies at 80 ℃ . Cyclic voltammetry (CV) and linear sweep voltammetry (LSV) revealed 5 reduction peaks, which were correlated with possible electrochemical or chemical reaction related to the formation of selenium. Potentiostatic electrodeposition using 100 mM SeO2 showed selenium nanorods formed at -0.389 V then increased in diameter up to -0.490 V, while more negative potentials (-0.594 V) induced formation of sub-micron wires with average diameter of 708 ± 116 nm. Submicron tubes of average diameter 744 ± 130 nm were deposited at -0.696 V. Finally, a mixture of tubes, wires, and particles was observed at more cathodic potential due to a combination of nucleation, growth, dissolution of structures as well as formation of amorphous selenium via comproportionation reaction. Texture coefficient as a function of applied potential described the preferred orientation of the sub-microstructures changed from (100) direction to more randomly oriented as more cathodic potentials were applied. Lower selenium precursor concentration lead to formation of nanowires only with smaller average diameters (124 ± 42 nm using 1 mM, 153 ± 46 nm using 10 mM SeO2 at -0.389 V). Time-dependent electrodeposition using 100 mM selenium precursor at -0.696 V explained selenium was formed first as amorphous, on top of which nucleation continued to form rods and wires, followed by preferential dissolution of the wire core to form tubes.